A shared medication scheme for community dwelling older patients with polypharmacy receiving home health care: role of the community pharmacist. Issue 5 (3rd September 2019) - Foubert, Katrien; Mehuys, Els; Claes, Leen; Van Den Abeele, Dirk; Haems, Marleen; Somers, Annemie; Petrovic, Mirko; Boussery, Koen
ABSTRACT: Background and objective : An accurate medication scheme may be a useful tool to improve medication safety in primary care. This study aimed to identify (1) pharmacists' alterations to nurse medication schemes and (2) potential improvements to the contribution of the community pharmacist to a shared medication scheme within a multidisciplinary collaboration. Dosing frequency, potentially incorrect moments of intake, drug–drug interactions and medication complexity (quantified by the Medication Regimen Complexity Index, MRCI) were investigated. Setting and method : Observational study in community dwelling older patients (≥70 years) with polypharmacy receiving home health care (i.e. medications being prepared and/or administered by home care nurses). Home care nurses provided the community pharmacist with the original medication scheme ('nurse medication scheme'), subsequently the community pharmacist generated a standardized 'pharmacist medication scheme' which was uploaded on an electronic health platform (Vitalink). The researcher recorded all pharmacists' alterations and looked for possible additional improvements ('researcher medication scheme'). Results : Pharmacists made 482 alterations to the nurse medication schemes of 31 patients. Most important alterations included adding indication (61%), generic or brand name (18%) and moment of intake (9%). Pharmacists did not reduce dosing frequency. MRCI scores (median [IQR]) significantly differed between pharmacist (38 [15]) and nurse medication schemes (32 [11]) ( p  < 0.001) and between nurse (32 [11]) and researcher medication schemes (40 [15]) ( p  < 0.001). Conclusion : Alterations made by the community pharmacists enable more complete and accurate medication schemes; however, there is room for improvement in optimizing the patient's medication scheme in a multidisciplinary collaboration.